2012
DOI: 10.1158/1078-0432.ccr-12-0178
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Phase II Clinical Trials with Single-Agent Therapies in Advanced/Metastatic Non–Small Cell Lung Cancer Published between 2000 and 2009

Abstract: Purpose: We analyzed the outcomes of single-agent phase II clinical trials in non-small cell lung cancer (NSCLC) to determine trial parameters that predicted clinical activity.Exoerimental Design: Data on response rate (RR), progression-free survival (PFS), and overall survival (OS) from all English language, single-agent phase II trials in advanced/metastatic NSCLC indexed by PubMed (January 2000 through December 2009) were abstracted.Results: A total of 143 single-agent phase II trials (7,701 patients) were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Further, a Cox regression analysis showed that being treated with a personalized strategy was an independent factor predicting a longer best PFS (median 10.3 vs. 7 months, P D 0.046) ( Table 4), consistent with several other studies demonstrating that adopting a personalized approach to treat cancer patients improved clinical outcomes. 1,38,39 Our study has several important limitations. The analysis was retrospective and included different types of cancer, although the latter might infer that the results are generalizable across tumor types.…”
Section: Discussionmentioning
confidence: 95%
“…Further, a Cox regression analysis showed that being treated with a personalized strategy was an independent factor predicting a longer best PFS (median 10.3 vs. 7 months, P D 0.046) ( Table 4), consistent with several other studies demonstrating that adopting a personalized approach to treat cancer patients improved clinical outcomes. 1,38,39 Our study has several important limitations. The analysis was retrospective and included different types of cancer, although the latter might infer that the results are generalizable across tumor types.…”
Section: Discussionmentioning
confidence: 95%
“…The RECIST 1.1 paper has been cited 3881 times as of December 2015 Web of Science. Endpoints categorized by the RECIST criteria have been used as either primary or supportive data for regulatory approval of new therapeutics by both the FDA and EMA [4]. RECIST provides a standardized set of rules for response assessment using tumour shrinkage, based upon imaging modalities that are globally available and interpretable by most clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…[1820] Further, a meta-analysis of the NSCLC literature showed responses of 49% when targeted treatments were matched to the appropriate subgroup of patients, but only 9.7% when unselected populations were treated. [21]…”
Section: Introductionmentioning
confidence: 99%